2018
DOI: 10.1016/j.jtcvs.2017.12.154
|View full text |Cite
|
Sign up to set email alerts
|

Sutureless aortic valve replacement with concomitant valvular surgery

Abstract: Perceval SU-AVR is a technically feasible and safe procedure in patients with severe aortic stenosis with good results even in the presence of multivalvular disease and atrial fibrillation surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…The significant reduction in time of implantation makes the sutureless valve a valuable adjunct in the case of double-valve procedures or need for concomitant atrial fibrillation ablation, as shown recently by Baran et al . 16 .…”
Section: Sutureless Aortic Valve Replacement: Technique and Resultsmentioning
confidence: 99%
“…The significant reduction in time of implantation makes the sutureless valve a valuable adjunct in the case of double-valve procedures or need for concomitant atrial fibrillation ablation, as shown recently by Baran et al . 16 .…”
Section: Sutureless Aortic Valve Replacement: Technique and Resultsmentioning
confidence: 99%
“…The largest series with Perceval valves was published by Baran et al showing 1 year survival rates >90%. 20 The rate of minor leakage 1þ or 2þ at discharge was 9.2 and 10% at 1 year. No higher grade leaks (>2 þ ) were registered in follow-up echo examinations.…”
Section: Discussionmentioning
confidence: 92%
“…Sutureless aortic prostheses have been suggested in cases of small aortic root and minimally invasive AVR, reducing cardiopulmonary bypass and clamp time with excellent hemodynamic performance and low rate of patient-prosthesis mismatch rather than conventional aortic valve prosthesis (2). Recently, sutureless prostheses have been also approved for their use in combined mitroaortic procedure and successful multivalvular implants have been reported (3).…”
Section: Clinical Results and Advantagesmentioning
confidence: 99%